PENERAPAN METODE PROJECT BASED LEARNING (PBL) DALAM MENGEMBANGKAN KREATIVITAS SISWA BELAJAR PAI DI SDN BARATAJAYA SURABAYA - Mardiyah; Fatmawati, Enie; Pardi (Jurnal Pendidikan Islam, 2023)
This article examines the application of the Project Based Learning (PBL) method in developing the creativity of students learning PAI at SDN Baratajaya Surabaya. This research is a qualitative descriptive study. The results showed that the application of the Project Based Learning Method can Develop the Creativity of Students studying PAI at SDN Baratajaya Surabaya is very good and appropriate because learning PAI using the Project Based Learning method is very interesting for students and developing their creativity is not boring in learning PAI which makes it easier for them to discuss and make works together with their group mates in a flexible time and then present them in front of the class, in addition to increasing their knowledge of PAI students can also develop their creativity, and the works they work on are exhibited at school report cards. The supporting and inhibiting factors in the application of the Project Based Learning (PBL) method are internal factors, including school principals, teachers, students and parents. External factors, including the surrounding community and the school environment. The school facilities and infrastructure/facilities are adequate, good enough to support students who are diligent in studying PAI, disciplined, responsible in doing their assignments well.